Exploring Human Rights Perspectives on Medical Cannabis Use in Indonesia: A Legal Analysis - Siti Syarifah Wafiqah Wardah (International Journal of Education, Vocational and Social Science, 2024)
Exploring Human Rights Perspectives on Medical Cannabis Use in Indonesia: A Legal Analysis. This research examines the perspective of human rights on the use of cannabis for medical purposes in Indonesia, focusing on normative legal analysis and related human rights views. It was found that while the medical use of cannabis can be justified by the right to health, there are still obstacles in its practice in Indonesia, especially regarding the provisions of Law No. 35/2009 which do not fully support the medical use of cannabis for healthcare services according to human rights perspectives.